2015
DOI: 10.3329/jme.v45i1.24384
|View full text |Cite
|
Sign up to set email alerts
|

ELECTROCHEMICAL CORROSION PERFORMANCE OF COMMERCIALLY USED ALUMINIUM ENGINE BLOCK AND PISTON IN 0.1M NaCl

Abstract: The corrosion behaviour of commercially used aluminium engine block and piston were investigated in 0.1M NaCl solution at room temperatures. The study was done by electrochemical method, using Tafel polarization and electrochemical impedance spectroscopy (EIS) techniques. The surface was characterized by optical microscope and scanning electron microscope (SEM). The results indicated differences in the charge transfer resistance of engine block and piston alloys. The current density (Icorr) of engine block mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 7 publications
1
12
0
Order By: Relevance
“…Hypereutectic aluminium-silicon alloys are used in applications that require high resistance to wear, corrosion, good mechanical properties, low thermal expansion and reduced density 1,2 . Their properties are of greatest attention to the automobile industry for the fabrication of fuel-efficient vehicles using light weight components produced from these alloys such as connecting rods, pistons, cylinder liners and engine blocks [3][4][5] .…”
Section: Introductionmentioning
confidence: 99%
“…Hypereutectic aluminium-silicon alloys are used in applications that require high resistance to wear, corrosion, good mechanical properties, low thermal expansion and reduced density 1,2 . Their properties are of greatest attention to the automobile industry for the fabrication of fuel-efficient vehicles using light weight components produced from these alloys such as connecting rods, pistons, cylinder liners and engine blocks [3][4][5] .…”
Section: Introductionmentioning
confidence: 99%
“…Higher content of nickel (from 0.31 to 1.1 %) and lower concentration of iron (from 0.59 to 0.77 %) in our alloys could explain the observed difference in E corr compared to the engine block alloy containing 0.083 % of nickel and 0.795 % of iron. 40 However, higher content of magnesium in our alloys (from 1.3 to 1.43 %) with regard to commercially available piston alloy containing 0.492 %, 40 could be the reason for the shift in the corrosion potential of about 114 or 122 mV to more negative values. Cyclic voltammetry was used to study the influence of chlorides on the oxidation and reduction processes at the surface of cast Al-Si alloys.…”
Section: Resultsmentioning
confidence: 71%
“…39 The significant differences in the values of corrosion potential of the examined alloys were not observed, whereas the lowest value of corrosion current was determined for alloy C. Kaiser et al studied the corrosion behaviour of the commercially available aluminium alloys for the manufacturing of an engine block and piston in 0.1 M NaCl solution. 40 The potentiodynamic polarisation study has shown the corrosion potential (E corr ) as -764 mV for the engine block alloy and -622 mV for the piston alloy. 40 The values of the corrosion potential obtained for our alloys were from -735.9 to -744.0 mV, which indicated a shift to more positive values, compared to an engine block alloy, but more negative values concerning the piston alloy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is degradation of materials' properties due to interactions with environments. Metal is converted into another compound such as oxide or salt by that reaction and leads to loss in desirable properties [10][11][12]. When tin is added to copper it forms oxides very rapidly which can perform as a superficial shear-strength film and has the ability to attenuate corrosion.…”
Section: Introductionmentioning
confidence: 99%